1987
DOI: 10.1021/ac00128a017
|View full text |Cite
|
Sign up to set email alerts
|

Transitory mobile phase environments for rapid selectivity changes in liquid chromatography: application to organic dyestuffs

Abstract: Transient mobile phase environments created by in|ectlng solvent plugs of varying composition are shown to selectively elute compounds according to their chemical properties. With several organic dyestuffs as model solutes, weakly acidic, strongly acidic, and neutral substances were sequentially eluted In a series of subchromatograms based on pH, Ion-pair competition, and hydrophobic Interaction mechanisms, respectively. Elution with both Isocratlc plugs and with pluggenerated gradients Is described. The use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This scheme resulted in improved resolution between the poorly separated solute peaks but had little or no effect on neighboring solutes. More recently, Gluckman and co-workers (26) have applied this method with acid-base, ion-pairing, and hydrophobic interactions to elute organic dyes selectively according to their chemical properties. In addition, the use of individual solvent zones has been examined in a computer simulation of whole-column detection by Gelderloos and co-workers (27).…”
Section: Literature Cited Introductionmentioning
confidence: 99%
“…This scheme resulted in improved resolution between the poorly separated solute peaks but had little or no effect on neighboring solutes. More recently, Gluckman and co-workers (26) have applied this method with acid-base, ion-pairing, and hydrophobic interactions to elute organic dyes selectively according to their chemical properties. In addition, the use of individual solvent zones has been examined in a computer simulation of whole-column detection by Gelderloos and co-workers (27).…”
Section: Literature Cited Introductionmentioning
confidence: 99%
“…Since a complete map of each peak's progress through the column would be produced by monitoring the separation process, selective separation could be carried out for overlapped peaks without regard to the possible degradation in resolution for previously quantitated peaks. Following our initiative, Gluckman and co-workers (11) employed solvent pulses for selective separation of organic dyes. They utilized a transparent column to view the separation of highly colored compounds and suggested that WCD would indeed provide substantially more useful information.…”
mentioning
confidence: 99%